2016
DOI: 10.3989/gya.0495151
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the sterol compositions of milk thistle oil (<em>Silybium marianum</em> L.) during seed maturation

Abstract: SUMMARY:In this study, the total lipid content and sterol compositions were determined during the development of milk thistle seeds. The oil content increased to a maximum value of 36±1.7% and then declined to reach a value of 30.5±0.9% at full maturity. The sterol content of milk thistle seeds was affected by the ripening degree of the seeds. At the early stages of seed maturation, Δ 7 -stigmastenol was the most abundant sterol followed by β-sitosterol. However, at full maturity, β-sitosterol was the most pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The other sterols were found in much lower amounts: Δ5-stigmasterol was at 0.25–0.35 mg/g, campesterol at 0.19–0.27 mg/g, and cholesterol at 0.12–0.37 mg/g; they constituted respectively 9–12%, 7–9%, and 4–13% of the total sterols. The individual sterol contents and their percentage compositions were in agreement with the results of studies of Harrabi et al ( 2016 ) and Fathi-Achachlouei and Azadmard-Damirchi ( 2009 ). In all dried samples, a decrease was observed in the total sterol contents (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The other sterols were found in much lower amounts: Δ5-stigmasterol was at 0.25–0.35 mg/g, campesterol at 0.19–0.27 mg/g, and cholesterol at 0.12–0.37 mg/g; they constituted respectively 9–12%, 7–9%, and 4–13% of the total sterols. The individual sterol contents and their percentage compositions were in agreement with the results of studies of Harrabi et al ( 2016 ) and Fathi-Achachlouei and Azadmard-Damirchi ( 2009 ). In all dried samples, a decrease was observed in the total sterol contents (Fig.…”
Section: Resultssupporting
confidence: 91%
“…They also protect against breast, colon and lung cancers (Woyengo et al 2009 ; Awad et al 2007 ). β-Sitosterol is the most predominant in milk thistle oil, follow campesterol and stigmasterol (Harrabi et al 2016 ). Tocopherols (α-, β-, γ- and δ-tocopherols and tocotrienols) have vitamin E activity.…”
Section: Introductionmentioning
confidence: 99%
“…The stronger antioxidant capacity of immature seed oil compared to mature seed oil may be due to the differences in their content and composition of unsaponifiable matter. In our previous study, we found that the amount of total unsaponifiable matter decreased during milk thistle seed maturation, while the total lipid content increased [ 29 ]. Additionally, Ramadan and Mörsel [ 42 ] reported a positive correlation between the radical scavenging activity of vegetable oils and their levels of unsaponifiables.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, certain Silybum marianum accessions have begun to be cultivated in several countries and the specie is undergoing domestication for making the supply of silymarin sustainable [ 28 ]. Previously published studies examined the triacylglycerol, fatty acid, tocopherol, sterol and polyhpenol composition of milk thistle seeds [ 10 , 26 , 29 32 ]. Significant differences were observed between milk thistle cultivars for the content of bioactive compounds [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained digitonides were filtered and washed with ethanol, and acetylation was performed (acetic acid anhydrous, with anhydrous sodium acetate, 2 h, 100 °C). Sterol acetates were crystallized from 50% ethanol (Jerzmanowska, 1967;Harrabi et al, 2016). Saponification of these mixtures yielded the free sterols which were identified by GC-MS.…”
Section: Extraction and Isolation Proceduresmentioning
confidence: 99%